The Implementation of BAHUMA is Being Done for Micro and Small Businesses of Individual Limited Liability Companies in Banjarmasin City - Syahrida, Syahrida; Yusman, Muhammad (Asean Study Center Lambung Mangkurat University, 2023)
Banjarmasin is a city of a thousand rivers, the potential of Micro and Small Enterprises (MSEs) in a wetland environment, in its readiness to face the challenges of world free trade, adjusting to new regulations, namely the Job Creation Law (UUCK). to get solutions in terms of ease of obtaining capital to improve the economy by utilizing natural resources, creating jobs with a creative economy that can improve the welfare of the community. This research describes and analyzes from a juridical perspective the policy of the Banjarmasin City Government in empowering MSEs related to the implementation of Individual Limited Liability Companies based on UUCK. The results of the research showed that: The policy of the Banjarmasin City Government in empowering the economy for individual PT micro businesses is in the form of providing People's Business Credit (KUR) through the BAHUMA (Bausaha Tanpa Bunga/ Business Without Interest) program based only on the Cooperation Agreement with PT Bank Kalsel Banjarmasin City Branch on Strengthening Micro Business Capital through the BAHUMA (Bausaha Tanpa Bunga/Business Without Interest) program. The business capital facilitation policy is a policy aimed at MSEs in general and not only at MSEs in the form of Limited Liability Companies (PT). There is no Banjarmasin City Government policy in the form of regional regulations or mayoral regulations that provide ease of financing for Individual PT MSEs in Banjarmasin City.